Cooperation Between Selawi Bambu Creative Center (SBCC) Mekarsari Village, Selawi District, Garut Regency And President Penyet Chicken Restaurant In Improving Cooperation Bambu Cooperation With Singapore In 2022-2023 - Sapitri R, Siti Salwa; Finaldin, Tom (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to examine the potential for cooperation in exporting bamboo crafts from Mekarsari Village, Selawi District, Garut Regency to Singapore. Mekarsari Village is known as a production center for unique and high quality bamboo crafts. Factors such as production sustainability, design innovation, and economic sustainability in Mekarsari Village are the focus of this research. The research methods used are interviews with bamboo craft industry players, surveys to assess production sustainability, and market analysis to evaluate export potential to chicken restaurants. President in Singapore. International Relations Explained Through Bilateral Cooperation Between Mekarsari Village and Export Partners of President's Chicken Restaurant in Singapore. This research article shows that Mekarsari Village has great potential to increase exports of bamboo crafts to President Chicken Restaurant in Singapore. Factors such as well managed production sustainability, design innovation that combines traditional and modern, and economic sustainability can be the main attraction for the international market. Strong Bilateral Cooperation Between Local Government, Industry Players, and Export Partners of the President's Chicken Restaurant in Singapore is the Key to Success in Developing the Export Market for Mekarsari Village Bamboo Craft Products. This research makes a positive contribution to local economic development and strengthens international relations between Mekarsari Village and Singapore and various other countries.